Study of protein-protein interactions of chromatin by immunoprecipitation (Experimental biology, 2015)
Different methods have been developed for the purpose of identifying and characterizing protein–protein interactions.There is a subset of methods based on proximity-dependent labeling of proteins in living cells. We propose a variation of proximity utilizing biotinylation technique that can be used to purify and study protein composition of chromatin inthe proximity to a nuclear protein of interest. It is based on co-expression of a protein of interest, fused with the bacterialbiotin ligase together with a histone fused to biotin acceptor peptide, which is specifically biotinylated by biotin ligase fusion in the proximity of the protein of interest. The proposed method is the only available method for the study of protein-protein interactions of chromatin in vivo.
Keywords: immunoprecipitation; chromatin; epigenetics; biotinylation; western-blot; mass spectrometry